Management of tooth loose with Cu-sil denture (case report): Penatalaksanaan kasus kehilangan gigi dengan Cu-sil denture (laporan kasus) - Melisa; Henni Koesmaningati; Muslita Indrasari (Makassar Dental Journal PDGI Makassar, 2022)
The success of denture treatment depends on the preservation of the remaining alveolar ridge. Preservation of the remaining na-tural teeth can assist in maintaining the integrity of alveolar ridge and proprioceptive ability of the periodontium. The main fo-cus in dentistry today is the maintenance of teeth and the periodontium. This case reports on the rehabilitation of a Cu-sil den-ture in the maxilla. A 70-year-old male patient wants to have denture because he wants to be able to eat and improve his appear-ance. The patient wants to preserve his remaining teeth as much as possible. It is concluded that Cu-sil denture can be an al-ternative treatment for patients who want to replace missing teeth while maintaining the remaining teeth.